Definizione e validazione del metodo di calcolo di un Indice di comfort delle sedie da ufficio / Definition and validation of a comfort index calculation method for office seats - Taboga, P.; Marcolin, F.; Bordignon, et al., M. (La Medicina del Lavoro, 2012)
Summary«Definition and validation of a comfort index calculation method for office seats». Background: Among its other required features, a highly comfortable chair should adapt its contact surfaces, namely the seat and the back rest, to the shape of the body of the person sitting on it. However, “comfort” is not usually perceived as an absolute value, but is derived from a subjective comparison between two or more chairs. Objectives: The purpose of this research was the definition of an objective comfort index (IC), i.e., derived from instrumental measurements, and which would also represent an absolute comfort value. Methods: Analytical evaluation of the distribution of body weight, by means of a barometric matrix, shows that a comfortable chair tends to minimize peak and average values of pressure at the level of the contact areas located between the body and the seat and the back of the chair. To define a comparison parameter for determining an absolute  comfort value, a reference chair (SDR) was developed. The seat and the back of this chair are rigid, with poor compliance. A comfort value of zero was, by definition, assigned to this chair. Therefore, the Comfort index (IC) was obtained by the mathematical calculation of the ratios of averages, peaks and gradients of pressure, appropriately weighted, and the corresponding values measured on the tested chair and on the SDR. Results: It is shown that the anthropometric characteristics of each subject are irrelevant to the assessment of the IC, which depends only on the compliance characteristics of the seat and back surfaces of the tested chair. Conclusions: IC can be improved through analysis of a larger number of seats, which would thus constitute the basis for the use of an objective evaluation of seating comfort.RiassuntoIntroduzione: Una sedia con un elevato grado di comfort avrà, tra le altre caratteristiche, la capacità di assecondare la forma delle superfici del corpo del soggetto che entrano in contatto con essa. Il comfort, tuttavia, non risulta una misura assoluta, ma un confronto soggettivo tra due o più sedili. Obiettivi: Scopo della ricerca è la definizione di un indice di comfort obiettivo, ossia derivato da misure strumentali, e assoluto. Metodi: La valutazione analitica della distribuzione del peso corporeo tramite tappetini barometrici ha evidenziato come un sedile confortevole tenda a minimizzare le pressioni medie, i picchi e i gradienti di pressione. Per poter definire un parametro di confronto assoluto del comfort si è definito un sedile di riferimento (SDR), rigido e scarsamente deformabile, a cui si è assegnato comfort nullo. L’indice di comfort (IC) definito dai rapporti tra le rispettive medie, picchi e gradienti di pressione, opportunamente pesati, sul piano di seduta e sullo schienale di sedile probando e SDR. Risultati: Si è evidenziato come le caratteristiche antropometriche dei singoli soggetti siano ininfluenti per la valutazione dell’IC, quest’ultimo essendo legato alle sole caratteristiche di compliance del sedile analizzato. Conclusioni: un affinamento dell’IC potrà venire soltanto dall’ampliamento del numero di sedute esaminate, costituendo quindi la premessa per un utilizzo ai fini della valutazione oggettiva del comfort dei sedili.